Phase-I cardiac rehabilitation practices among physiotherapists in INDIA - A survey - chari, Shruti; Alaparthi, Gopala Krishna; K, Shyam Krishnan; prabhakar, Ashish; Bairapareddy, Kalyana Chakravarthy (Bangladesh Journal of Medical Science, 2020)
Objective: To find out the current practice patterns of Physiotherapists in Phase I Cardiac Rehabilitation of patients following Cardiac Surgery (CABG/Valve Surgery). Materials and Methods: The cross sectional survey included 600 cardio-pulmonary physiotherapists working in Cardiac Care Unit, who filled questionnaires sent to them through e-mail. Results: 252 completed questionnaires were received back, the response rate being of 42 %, with a major portion of responses coming from Maharashtra, Karnataka and Andhra Pradesh. More than 80 % of physiotherapists assess and treat the patient Pre- Operatively. More than 90% of physiotherapists performed Cardiac Rehabilitation Post-Operatively. Cardiac Rehabilitation Treatment Techniques predominantly focused on Breathing Exercises (96.7%), Incentive Spirometry (91.1%), Coughing and Huffing (83.3%), Thoracic Expansion Exercises (82.13%), Positioning (71.16%), Percussion and Vibration (63.6%), Modified Postural Drainage (41.2%), active exercises of the upper limb (89.13%), and lower limb exercises (89.3%). Dangling the lower limb (69%) was started on Post –Operative day 2. Room and corridor mobilisation (73.8%) began on third Post-Operative day. 29.4% Stair case climbing was started on fourth post-operative day. 73.8% of patients practiced 6-minute walk test prior to discharge. Most commonly used sternal precautions were Supported Coughing (96.0%) and Lifting Restrictions (82.5%). Conclusion: Phase I cardiac rehabilitation adopted by physiotherapists for cardiac surgery patients involves treatment which mainly focused on cough and huff techniques, breathing exercises and thoracic expansion exercises. On Post-Operative day 2, dangling the lower limb and room ambulation started on third post-Operative day 3. The training for climbing stairs started on fourthpost-operative day. The most commonly used sternal precautions were supported coughing and lifting restrictions whereas 6-minute walk test was use to assess exercise tolerance,prior to discharge. Bangladesh Journal of Medical Science Vol.19(2) 2020 p.214-222